INFLUENCE OF INSTAGRAM SOCIAL MEDIA ON CUSTOMER LOYALTY AT LAIDBACK BLUES RECORD STORE - Emenina Tarigan; Ervina Taviprawati; Reno Abireksa (Universitas Islam Lamongan, 2022)
This study aims to determine the effect of Instagram social media on customer loyalty at Laidback Blues Record Store. This type of research is descriptive quantitative with simple regression analysis method. The population in this study were followers of the Instagram account @laidbackbluesrecordstore during 2021, which opened 150 people, while the sample consisted of 60 using the slovin formula. The sampling technique used in this study is non-probability sampling. Questionnaire data collection techniques using google form. The results showed that Instagram social media had a significant effect on customer loyalty at Laidback Blues Record Store. This is because the Laidback Blues Record Store social media is always active in observing so that interaction with consumers is maintained and consumers actively comment on, make complaints, about products, provide suggestions, or activities that are being carried out. Laidback Blues Record Store is advised to improve the presentation of the latest information regarding product promotions that can be carried out actively